Effectiveness of digital storytelling comics based on a deep learning approach in enhancing environmental awareness among elementary school students - Wirastusrini Tjakrawerdaja; Firmanul Catur Wibowo; Cecep Kustandi; Beken Arymbekov (Education and Development Research, 2025)
Environmental awareness in elementary school students generally still focuses on cognitive knowledge, without being followed by reflective understanding or real behavior in daily life. This condition highlights a gap in environmental education practices, particularly the lack of integration between affective and behavioral aspects, indicating a need for a learning strategy that fosters a meaningful attitude of environmental care. This study examined the effectiveness of immersive digital storytelling comics developed based on a deep learning approach in enhancing environmental awareness among elementary school students. The method used is quasi-experimental with a pretest-posttest design model. The research subjects consisted of 34 grade V students at one of the East Jakarta public elementary schools in the even semester of the 2024/2025 school year. The instrument is in the form of an environmental awareness questionnaire compiled based on indicators of environmental care attitudes, supported by observations and interviews. Data were analyzed descriptively, using paired t-tests, and N-Gain calculations. The results revealed a significant increase in environmental awareness, with the average score increasing from 42.06 (pretest) to 83.09 (posttest), and p<0.001. The N-Gain analysis of 71.40% indicates a high level of improvement. These findings demonstrate that integrating digital storytelling comics with a deep learning pedagogical approach effectively fosters environmental understanding, empathy, and pro-environmental behavior among elementary school students.